Close Reading with Computers Textual Scholarship, Computational Formalism, and David Mitchell's Cloud Atlas - Eve, Martin Paul (Stanford University Press, 2019)
Rather than working at the usual scales of distant reading, this book shows what happens when we bring techniques from the digital humanities to bear on a single novel for close readings.